Dynamics of span morphing helicopter rotor - Vangeti, D.; Murugan, M.S. (My University, 2021)
Variable span morphing rotor blade can vary its radius during the flight and can improve the flight performance and flight dynamics significantly. In this study, the dynamics of a span morphing rotor blade is modeled and analysed. A telescopic-box beam type mechanism is considered for realizing the span morphing blade. The telescopic wing had two beams, a primary beam attached to the rotor hub and a secondary beam that can morph along radial direction. The dynamics induced by span morphing is captured as moving loads over the primary beam. The morphing dynamic equations are derived using the approximate energy methods. The effect of key morphing parameters such as span morphing speed, magnitude of morphing loads and rotor speed on the flap dynamic response of primary beam are studied. Results show that the speed of span morphing has significant impact on the flap dynamic response. Also, the magnitudes of span morphing loads have considerable impact. In contrast, rotor speed during span morphing has inverse effects on the flap response because of the coupled effect of loss of centrifugal stiffness and addition of morphing induced dynamic loads. Therefore, in general, the morphing induced dynamics plays a significant role in the design of span morphing rotor.